2001
DOI: 10.1007/s004170100341
|View full text |Cite
|
Sign up to set email alerts
|

Ocular toxicity study of trypan blue injected into the vitreous cavity of rabbit eyes

Abstract: Although no signs of toxicity were found after the prolonged presence of TB at a concentration of 0.06% in the vitreous cavity of rabbit eyes, marked damage occurred in the lower retina of 0.2% TB-treated eyes. The short-term presence of TB at a concentration of 0.06% in the vitreous cavity is harmless to the rabbit eye but a higher concentration of TB could be unsafe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
2
10

Year Published

2002
2002
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(90 citation statements)
references
References 7 publications
2
76
2
10
Order By: Relevance
“…[13][14][15] The safety of intravitreal application of Tb has also been demonstrated in rabbit studies. 16 Recently, Tb has been shown to be a useful intraoperative agent for improving the visualisation and complete removal of peripheral ERM in patients with proliferative vitreoretinopathy. 17 Tb has also been suggested to be useful in staining macular ERM and internal limiting membrane (ILM) in cases of macular hole and macular pucker.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The safety of intravitreal application of Tb has also been demonstrated in rabbit studies. 16 Recently, Tb has been shown to be a useful intraoperative agent for improving the visualisation and complete removal of peripheral ERM in patients with proliferative vitreoretinopathy. 17 Tb has also been suggested to be useful in staining macular ERM and internal limiting membrane (ILM) in cases of macular hole and macular pucker.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 It can be argued that the loss in VA of some of the patients was potentially due to dye toxicity. However, Veekeneer et al, 8 investigating toxicity of Trypan blue at various concentrations (0.2 and 0.06%) found that only at 0.2% did Trypan blue show any signs of toxicity, manifest as damaged photoreceptors and marked disorganization with light and electron microscopy and reduced immunohistochemical staining for rhodopsin. At 0.06% concentration of Trypan blue (the concentration of Trypan blue available as VB) was concluded to be harmless.…”
Section: Discussionmentioning
confidence: 99%
“…4 As compared with ICG, Trypan blue appears to have a broader safety profile, as it is non-toxic to cultured retinal pigment epithelial cells and glial cells at concentrations used clinically between 0.06 and 0.2%, and is non-toxic to rabbit retina when it is promptly removed. 18,23,[25][26][27] . Compared with ICG, it is easier to remove from the vitreous cavity, given its high water solubility.…”
Section: Discussionmentioning
confidence: 99%